African Americans and the Self-help Revolution: A missing link in adult education - Michael L. Rowland (Adult Education Research Conference, 2001)
This roundtable discussion will recognize the significant role of self-help education and self-help literature in the lives of African American adults and to determine ways for adult educators to expand our knowledge base of self-help education for African Americans.